Maternal flower color, ultraviolet protection, and germination in Ipomopsis aggregata (Polemoniaceae). Issue 2 (13th January 2022) - DiBiase, Charlotte; Godtfredsen, Elsa; Dahl, Julian; Shapiro, Alex; Brown, Keirsten; Martin, Amanda; Wermuth, Anna; Heschel, M. Shane
Abstract: Transgenerational interactions between flower color, seed quality, and seedling performance have rarely been investigated. The ecological model, Ipomopsis aggregata, is a great candidate for examining the maternal effects of flower color because it is a mostly scarlet‐flowering plant which shows color polymorphism within natural populations. Anthocyanin, the red flavonoid pigment which gives these flowers color, has been shown to act as an ultraviolet (UV) protectant by shielding chloroplasts and acting as an antioxidant. This study was conducted on scarlet‐ and fuchsia‐flowering maternal plants and their seeds from natural populations in Colorado. Dark‐flowering (scarlet) maternal plants from these populations had consistently higher foliar anthocyanin content, photosystem efficiency, and chlorophyll content than light‐flowering (fuchsia) plants over a 3‐year period in the field. Seeds from a subset of these maternal plants were counted, weighed, and germinated in a growth chamber. Photosystem efficiency, vegetative anthocyanin content, chlorophyll content, and biomass were measured on germinated seedlings after the germination census was completed. Dark‐flowering maternal plants yielded seeds and seedlings with higher biomass than light‐flowering ones. Seeds from dark‐flowering maternal plants also germinated faster than those from light‐flowering maternal plants and seedlings had higher vegetative anthocyanin content. The hereditary nature of anthocyanin content thus suggests that higher anthocyanin levels (both floral and vegetative) are potentially linked to measures of fitness such as increased seed weight, germination rate, and seedling biomass. These data suggest that UV protection provided by anthocyanins potentially increases the realized fitness of maternal plants, thereby influencing life history. Abstract : Dark‐flowering (scarlet) maternal plants yielded seeds and seedlings with higher biomass than light‐flowering (fuchsia) ones. Seeds from dark‐flowering maternal plants also germinated faster than those from light‐flowering maternal plants and had higher anthocyanin content. These data indicate that ultraviolet protection provided by anthocyanins potentially increases the realized fitness of maternal plants, thereby influencing life history.